Water and Otolith Chemistry: Implications for Discerning Estuarine Nursery Habitat Use of a Juvenile Flatfish - Martinho, Filipe; Pina, Beatriz; Nunes, Margarida; Vasconcelos, Rita P.; Fonseca, Vanessa F.; Crespo, Daniel; Primo, Ana Lígia; Vaz, Ana; Pardal, Miguel A.; Gillanders, Bronwyn M.; Tanner, Susanne E.; Reis-Santos, Patrick (Frontiers in Marine Science, 2020)
Variations in otolith elemental composition are widely used to reconstruct fish movements. However, reconstructing habitat use and environmental histories of fishes within estuaries is still a major challenge due to the dynamic nature of these coastal environments. In this study, we performed a laboratory experiment to investigate the effects of variations in salinity (3 levels; 5, 18, 30) and temperature (2 levels; 16ºC, 21ºC) in the otolith elemental composition (Mg:Ca, Mn:Ca, Sr:Ca, Ba:Ca) of juvenile Senegalese sole Solea senegalensis. Temperature and salinity treatments mirrored the natural conditions of the estuarine habitats generally occupied by juvenile Senegalese sole, thereby providing information on the applicability of otolith microchemistry to reconstruct habitat use patterns within estuarine nurseries, where individual fish move across complex salinity and temperature gradients. While Sr:Ca and Ba:Ca in otoliths were both positively related to salinity, no temperature effect was observed. Partition coefficients, proxies for element incorporation rates increased with increasing salinity for Sr (DSr) and Ba (DBa). In contrast, salinity and temperature had little influence on otolith Mn:Ca and Mg:Ca, supporting physiological control on the incorporation of these elements. Our results are a stepping stone for the interpretation of otolith chemical profiles for fish collected in their natural habitats and contribute to better understanding the processes involved in otolith element incorporation.